The EFFECT OF CAPITAL STRUCTURE, INFLUENCE OF AMOUNT AND DEVELOPMENT ON BUSINESS VALUE MODERATION GCG SUBJECT FOOD AND BEVERAGE COMPANIES ON BEI 2016 - 2020 - Aditya Angger Wibowo (WORLDVIEW ( Development economic and sharia studies journal ), 2024)
The aim of this research is to find out how capital structure, the influence of size and development influence business value which is moderated by GCG. This quantitative research approach uses secondary data about 30 food and beverage companies listed on the IDX from 2016 to 2020 and samples were taken from seven companies, the data collection technique used purposive sampling technique. Data processing analysis uses the partial least square PLS technique using the smart PLS application. The research results show that GCG influences capital structure directly and significantly; size and development are not directly and significantly influenced by GCG; business value is not directly and significantly influenced by GCG; and the amount does not affect ownership directly or significantly.